Properties of particleboard from oil palm trunk in relation to various sizes of particles / Fatin Nadhirah Mohamad - Mohamad, Fatin Nadhirah (Faculty of Applied Sciences, 2016)
This project was carried out to study about the properties of particleboard by using oil palm trunk. Oil palm trunk is the new species that has a potential to be commercialized as the raw material in wood based industry as it is the species that is most planted in the country. In line with the need to further exploit the potential use of oil palm, this study was undertaken to investigate the feasibility of the species in particleboard manufacturing. For this study, three particles sizes of 1 mm, 2 mm and unscreening particles sizes from oil palm trunk were blended with phenol formaldhyde (PF). In general this particleboard was significant with various sizes of particles oil palm trunk. The particleboard was determined by mechanical properties and physical properties. These result showed that unscreening size has better performance in bending and internal bonding strength meanwhile 1 mm size has better in thickness swelling and small size should not be used for mechanical properties of particleboard